Evaluation of Postoperative Pain and Discomfort in Patients Undergoing Surgical Exposure of Impacted Maxillary Canines - Gryte Zabielskaite; Mariam Varoneckaite; Dalia Smailiene (Stilus Optimus, 2022)
Objectives: The purpose of the retrospective study was to evaluate pain and discomfort related to surgical exposure according to initial localization of impacted maxillary canines. Material and Methods: Pre-treatment cone-beam computed tomography (CBCT) data and discomfort evaluation questionnaire of 25 patients (17 female, 8 male), treated with combined surgical-orthodontic approach was analysed. The questions included: level of discomfort during surgery (0 to 10), level of pain (0 to 10) in the evening, one, two days and a week after surgery. CBCT analysis consisted of evaluation of impacted maxillary canines mesiodistal inclination, horizontal, vertical dislocation from alveolar process edge, labiopalatal localization and length of eruption path. To carry out research objectives a Spearman and interclass correlation coefficients, Mann-Whitney U test, Cohen's kappa coefficient were used. Level of significance was 0.05. Results: Average level of discomfort during the procedure was 2.8 (SD 2.3). Pain level the evening after the surgery was the highest - 3.3 (SD 2.1) and decreased over the week. Pain level differed significantly between different days (P < 0.001). Neither labial or palatal location nor the unilateral or bilateral impaction had effect on the level of pain (P > 0.05). The results showed that pain during different stages of measuring as well as level of discomfort during surgical exposure did not differ statistically significantly depending on severity of impaction (P > 0.05). Conclusions: There was no significant relation between the discomfort and the location of the impacted canine. Patient's gender or age did not have an impact on discomfort and pain.